Pre-Partum Feeding and Elimination Behaviour of Kankrej Cows at an Organized Farm - SRIVASTAVA, AMIT KUMAR; Patel, J.B.; Chaudhary, A.P.; Ankuya, Kanubhai J; Chauhan, Haresh D; Patel, Vikram K; Gupta, Jay Prakash; Pawar, Mahesh M (Indian Journal of Animal Production and Management, 2024)
Present study was carried out to assess the effect of parturition on feeding behaviour on before calving. 21 Kankrej cows were equally grouped into 3 treatments, first parity (T1), second parity (T2) and 3 or more parity (T3) cows. The behaviour of cows was recorded with two CCTV cameras and 24 hours’ observations were made from recorded video for four days −1, −2, −3 and −7 prior to the calving. The feeding behaviour was assessed in terms of feeding frequency, feeding duration and watering frequency. The mean feeding frequency was the highest on the day of calving (30.33±2.07) followed by day-3 (26.62±1.43), day-2 (25.33±1.46) and Day-7 (24.43±1.40) in a day and the difference found was significant (P